Letters written during a short residence in Sweden, Norway, and Denmark - Wollstonecraft, Mary, 1759-1797 (Oxford University Press, 2009)
Letters written during a short residence in Sweden, Norway, and Denmark (1796) is both an arresting travel book and a personal memoir. In it Wollstonecraft describes the sublime landscape and the events and people she encounters. This edition includes reviews, additional letters, and documents on the background to the journey. - ;'If ever there was a book calculated to make a man in love with its author, this appears to me to be the book.'William Godwin, the author's future husband, was not alone in admiring Letters written during a short residence in Sweden, Norway, and Denmark, Wollstonecraf.
Keywords: Wollstonecraft, Mary, -- 1759-1797 -- Travel -- Scandinavia.; Wollstonecraft, Mary, -- 1759-1797. -- Correspondence.; Imlay, Gilbert, -- 1754?-1828? -- Correspondence.; Wollstonecraft, Mary, -- 1759-1797; Correspondence (Wollstonecraft, Mary); Scandinavia -- Description and travel -- Early works to 1800.; Authors, English -- 18th century -- Correspondence.; Feminists -- Great Britain -- Correspondence.; Scandinavie -- Descriptions et voyages -- Ouvrages avant 1800.; Écrivains anglais -- 18e siècle -- Correspondance.; Féministes -- Grande-Bretagne -- Correspondance.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; BIOGRAPHY & AUTOBIOGRAPHY -- Literary.; Authors, English; Feminists; Travel; Great Britain; Scandinavia; 1700-1799; autobiographies (literary works); Autobiographies; Early works; Personal correspondence; Autobiographies.